VD_FINDINFO Jug / 2021 / 78 vom 18. August 2020 - VD Tribunal cantonal (2020)
CONSTATATION DES FAITS, MISE EN DANGER DE LA VIE D'AUTRUIART. 129 CP, TENTATIVE SIMPLE, MEURTRE, EXPULSIONDROIT PÉNAL, TORT MORAL | 129 CP, 22 ad 111 CP, 66a al. 1 let. a CP, 66a al. 1 let. b CP, 66a al. 2 CP, 10 CPP (CH)